Literasi Digital dan Implikasinya terhadap Pemahaman Fikih Ibadah Mahasiswa PAI di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) - St. Najma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Abstract This study aims to analyze the level of digital literacy among students of the Islamic Religious Education (PAI) study program at State Islamic Higher Education Institutions (PTKIN) and its implications for the quality of their understanding of fiqh al-ibadah. Employing a descriptive qualitative approach with data collection techniques comprising comprehensive literature study and analysis of student digital behavior trends, this research identifies two poles interacting dynamically: on one hand, the expansion of access to religious content through digital platforms has opened unprecedented opportunities for democratizing Islamic jurisprudence knowledge; on the other, the tendency toward instant content consumption potentially reduces depth of understanding of ijtihad methodology and classical fiqh epistemology. Findings indicate that PAI students generally possess adequate technical digital skills, yet remain weak in the critical literacy dimension namely the ability to evaluate the validity, authority, and religious context of digital sources. This phenomenon produces a literacy paradox: students who appear